STUDY SUCCES AS A FUNCTION OF OUT-OF-SCHOOL SPORTS ACTIVITIES - Marianna MORAVECZ; Ágoston NAGY (Cluj University Press, 2019)
Study success is usually closely related to the popularity of certain subjects and the sport activities. The purpose of our study is to highlight the connection between the participation of students in out-of-school sports activities and their success in school on the basis of the analysis of the 10th-year student questionnaires of the 2016 OKM database. In our research we examine the correlation between sport activities and gender using cross tables. For forming student groups, we used cluster analysis, for analysing the factors of participation in extracurricular sport classes we used logistic regression analysis, and for analysing the factors influencing grade point average we used linear regression analysis. As for out-of-school extra and private lessons, according to our results sports activities seem to be the most popular with students. Concerning gender and school grade average, boys and students with a better school grade average take part in sports activities unlike girls and students with lower school grade average. Regression results have shown that boys, those living in the city, the more financially well-off, the highly educated and the labour-marketed parents, those attending grammar school, and pupils in church-based institutions attend extra-curricular sports classes. There is also a strong correlation between the average education and non-school sports, as students with a higher average grade are involved in separate sports classes.